0174 Mortality due to asbestosis in a cohort of former asbestos textile workers. (21st August 2017) - Farioli, Andrea; Violante, Francesco Saverio; Vecchia, Carlo La; Negri, Eva; Pelucchi, Claudio; Spatari, Giovanna; Boffetta, Paolo; Pira, Enrico
Abstract : Background: Knowledge on the role of the temporal pattern of exposure to asbestos in determining mortality from asbestosis is limited. We aim at investigating how the risk of death due to asbestosis changes according to the duration of employment and the time since the last employment (TSLE). Methods: An historical cohort of workers from a former asbestos textile factory (active between 1946 and 84) was followed up until November 2013. For each subjects, we collected information on duration of the employment, TSLE, age and year of first employment, and sex. We estimated hazard ratios (HR) and 95% confidence intervals (CI) of death from asbestosis by fitting multivariable Cox regression models with age specified as the main temporal axis. Results: We identified 51 deaths from asbestosis that occurred among 1823 workers (incidence rate of 74 cases per 1 00 000 person-years). The risk of death from asbestosis increased with increasing exposure duration (HR 3.0 [95%CI 1.3–7.6] for duration of employment ≥15 years compared to duration <5 years) and declined with TSLE (HR 0.3 [95%CI 0.1–0.9] for TSLE ≥25 compared to TSLE <5 years). We observed a strong decline of mortality due to asbestosis among workers firstly employed after 1968. Conclusions: Information on the temporal pattern of exposure to asbestos is fundamental to estimate the individual risk of asbestosis. On the opposite of what overserved in ecological studies, the risk of death due to asbestosis declines steadily after cessation of exposure to asbestos.